THE INFLUENCE OF PRODUCT PACKAGING AND FEATURES TO THE PURCHASE ANDROID SMARTPHONE - IAN NURPATRIA SURYAWAN; STEFANI STEFANI; SETIA TJAHYANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2013)
Several things are to determine by choice of consumers on smartphone is processor speeds, to run an application the amount of memory, the magnitude of storage capacity, the degree of clarity during the screen to the degree of clarity camera, the prices of service purna sell, and the ease of use. This time the system of operations much used is android. Every manufacturer smartphone trying to keep smartphone the results of its production be the best in the market. Hence, producer smartphone uses advertising, distribution and cooperation with several operators to attract customers. Each company smartphone having identification and market segmentation cloistral. The purpose of the study is to provide empirical evidence of the influence of the features and packaging of the product on purchasing decisions Smartphone. The results of this study demonstrate the look of the product affect the purchasing decisions Smartphone. While, Smartphone product features do not have influence on product purchase Smartphones.